Emma and Julia love ballet - McClintock, Barbara 1955- (Scholastic Press, 2016)
A story that follows the everyday life of two girls, one a professional ballerina, the other a student, both of whom love ballet
Keywords: Ballet dancers -- Juvenile fiction; Ballet -- Juvenile fiction; Dance recitals -- Juvenile fiction; Ballet dancing; Ballet; Tänzerin; Aufführung; Ballett; Bilderbuch